Glare indicators: an analysis of ocular behaviour in an office equipped with venetian blinds - Yamin Garretón, Julieta Alejandra (2014)
This article studies the ocular behaviour of office workers in the presence of glare. Additionally, the study seeks to obtain a new indicator for glare prediction that compensates the inaccuracies of glare predicted by the existing models of glare sensation vote (GSV), daylight glare probability (DGP) and daylight glare index. A laboratory experiment was carried out (n=18) simulating an office space. The volunteers participated in four office tasks (reading from a screen and from a paper, writing and socializing). Two scenarios were evaluated: one with sunspots on the faces of the subjects and the other with sunspots on the working area. By means of a visible spectrum eye tracker these ocular parameters were registered: direction of gaze, the degree of opening of eye and pupil size. These ocular parameters were correlated with vertical illuminance at the eye. The results show that the degree of reduction of opening of the eye was the best predictor of visual discomfort with statistically significant differences between scenarios (p=?0.728, s =0.001). The other important predictor was the pupil size. The degree of opening of eye and pupil size was correlated with glare indices. The degree of eye opening has a good correlation with GSV and DGP and it could be a future index of visual comfort under situations of the risk of glare.